EFFECT OF SPENT ENGINE OIL ON THE MORPHOLOGICAL GROWTH INDICES OF GROUNDNUT (ARACHIS HYPOGEA L.) IN KEFFI LOCAL GOVERNMENT AREA OF NASARAWA STATE. - Maijarmiya, M A; Ibrahim, H A; Umar, Y I (Research Journal of Agriculture (RJA), 2025)
This study investigates the impact of spent engine oil (SEO) contamination on the morphological growth indices of Arachis hypogaea (groundnut) in Keffi, Nigeria. Groundnut, a vital crop for nutrition and economic sustainability, often faces challenges from soil pollutants, including hydrocarbons from used engine oil. The experiment involved cultivating groundnuts in soil treated with varying concentrations of SEO (0%, 3%, 6%, and 9%) to evaluate its effects on plant height, leaf dimensions, branch number, and yield. Results demonstrated a concentration-dependent decline in growth and yield, with the control group consistently outperforming polluted treatments. Interestingly, the 3% SEO treatment resulted in increased leaf length compared with the control, suggesting complex interactions at lower pollution levels. The findings underscore the harmful effects of SEO on crop productivity, emphasizing the need for proper waste management practices to protect agricultural resources. This research provides valuable insights into mitigating pollution’s impact on food security and sustainable farming